The effects of low- and high-intensity exercise on Holstein dairy cattle muscle composition and thermoregulatory capabilities - Schettler, Keleigh Amaris (Kansas State University, 2020)
Heat stress, the inability of the body to maintain thermal homeostasis, is one of the most significant health challenges that faces the dairy industry. The economic impact of heat stress has cost the dairy industry an estimated $1-$2 billion per year. Mitigation of heat stress on dairy herds is essential to the success of the industry and welfare of the cattle. One proposed strategy for mitigation of heat stress is exercise-induced heat acclimation. In humans, rats, and horses, exercise has been documented as promoting changes in skeletal muscle fiber types and vasculature that are more conducive to maintaining homeostatic temperatures. To test the utility of exercise as a method to mitigate heat stress, three 8-week exercise trials involving a total of 71 Holstein dairy heifers were completed over a two-year period; the first trial (trial 1) occurred during the early summer of 2016, the second (trial 2) during the late summer of 2016, and the third (trial 3) during the early summer of 2017. Trial 1 and 3 heifers were kept in drylot pens before trial commencement, while trial 2 heifers were kept on multi-acre pasture. Heifers were split into groups within trials 1 and 2 to perform one of three activities: sedentary, low-intensity exercise, or high-intensity exercise. Heifers in trial 3 in 2017 performed only sedentary or low-intensity exercise treatments. Skeletal muscle composition of biopsies from the semitendinosus (Chapter 2; trial 1 and 2) and biceps femoris (Chapter 3; trial 3) muscles were analyzed within and across treatments. Chapter 2 data were combined for analysis utilizing a randomized complete block design to account for differences between trial. Percentage of fiber types, cross-sectional surface area, and oxidative capacity were measured for Chapters 2 and 3, with capillary density being an additional measurement for Chapter 3. In addition, for Chapter 3, core body temperature (via rectal thermometer) and mean skin temperature (via infrared thermometer) were obtained weekly, and ear temperatures from CowManager Sensors were obtained hourly. Time by treatment interactions were analyzed via a two-way repeated measures ANOVA for body weight, fiber type percentages, cross-sectional surface area, oxidative capacity, and temperature data. For Chapter 2, there were no time by treatment interactions of fiber type percentages, indicating that time and type of exercise did not affect fiber type percentages; however, in Chapter 3 there was a time by treatment interaction for type I fiber percentages, with sedentary treatment decreasing type I fibers over time and low-intensity treatment increasing type I fiber percentages. Cross-sectional surface area and oxidative capacity of fiber types were unaffected in Chapters 2 and 3 and capillary density was unaffected by exercise treatment in Chapter 3. In Chapter 3, temperature data were evaluated for mean skin temperature to core body temperature ratio, temperature trends during a period of ambient cooling, and temperature trends during a period of ambient heating. There was a time by treatment interaction for the temperature data during the period of cooling; heifers that underwent low-intensity treatment had lower temperatures during the cooling period than those completing sedentary treatment. Additionally, the sensitivity of the CowManager ear tags were compared with rectal temperatures (core body temperatures) and infrared temperatures of the left ear (ear temperature); this occurred to determine if the ear tags were sensitive enough to detect minute differences between treatments after a period of exercise. As there were differences between treatments indicated by rectal temperatures, but not by the ear tags, and, as temperature trends wavered depending on the obtainment method, we concluded that the ear tags are not sensitive enough to detect differences in body temperature after periods of exercise. Both high and low-intensity exercise did not seem to consistently effect skeletal muscle among Chapters 2 and 3; however, Chapter 3 data analyses did show promise with low-intensity exercise potentially improving cooling capabilities during a period of ambient cooling. Additionally, CowManager ear tags may not be beneficial in determining the differences in body temperature after a period exercise. Further investigation into the effects of exercise on fatty liver disease and urine-nitrogen content may be warranted, as well as investigation into utilizing longer trial periods for dairy cattle exercise.
Keywords: Dairy; Exercise; Muscle fibers; Thermoregulation